Benzothiazoles from Condensation of o-Aminothiophenoles with Carboxylic Acids and Their Derivatives: A Review - Efrén V. García-Báez; Itzia I. Padilla-Martínez; Feliciano Tamay-Cach; Alejandro Cruz (Molecules, 2021)
Nowadays, organic chemists are interested in the field of heterocyclic chemistry due to its use in the synthesis of a great variety of biologically active compounds. Heterocyclic compounds are widely found in nature and are essential for life. Among these, some natural nitrogen containing heterocyclic compounds have been used as chemotherapeutic agents. Their attachment to sugar molecules either as thioglycosides or as nucleosides analogues plays an important role in vital biological processes as well as in synthetic organic chemistry. Molecules containing benzothiazole (BT) nuclei are of this interesting class of compounds because some of them have been found to have a wide variety of biological activities. In this sense, we selected this topic to review and to then summarize the procedures related to the condensation reactions of o-aminothiophenoles (ATPs) as well as their disulfides with carboxylic acids, esters, orthoesters, acyl chlorides, amides, and nitriles. The condensation reactions with carbon dioxide (CO2) are included. Conventional methods with the use of acid and metal catalysts as well as recent green techniques, such as microwave irradiation, the use of ionic liquids, and ultrasound (US) chemistry, which have proven to have many advantages, were found in the review.